Inhibitory networks of the amygdala for emotional memory - Lee, Seungho; Kim, Su-Jeong; Kwon, Oh-Bin; Lee, Joo Han; Kim, Joung-Hun (Frontiers in Neural Circuits, 2013)
The amygdala is important for emotional memory, including learned fear. A number of studies for amygdala neural circuits that underlie fear conditioning have elucidated specific cellular and molecular mechanisms of emotional memory. Recent technical advances such as optogenetic approaches have not only confirmed the importance of excitatory circuits in fear conditioning, but have also shed new light for a direct role of inhibitory circuits in both the acquisition and extinction of fear memory in addition to their role in fine tuning of excitatory neural circuitry. As a result, the circuits in amygdala could be drawn more elaborately, and it led us to understand how fear or extinction memories are formed in the detailed circuit level, and various neuromodulators affect these circuit activities, inducing subtle behavioral changes.